Privatising Basic Utilities in Sub-Saharan Africa: The MDG Impact - Bayliss, Kate (2007)
This policy research brief draws on the findings of a UNDP-supported book, Privatization and Alternative Public Sector Reform in Sub-Saharan Africa (Bayliss and Fine, forthcoming), to analyse the effects of privatisation on the delivery of water and electricity. Its chief conclusion? Privatisation has been a widespread failure. This has hampered progress on the MDGs for both water and sanitation, and on many other MDGs dependent on energy. (...)